Cacao residues in vessels from Chocolá, an early Maya polity in the southern Guatemalan piedmont, determined by semi-quantitative testing and high-performance liquid chromatography. (June 2017) - Kaplan, Jonathan; Paredes Umaña, Federico; Hurst, W. Jeffrey; Sun, D.; Stanley, Bruce; Barba Pingarrón, Luis; Obregon Cardona, Mauricio
Abstract: Adding to a thus far limited number of archaeological identifications of cacao residues in pottery in ancient Mesoamerica, this study presents the first such evidence from the southern Guatemalan piedmont in the Southern Maya Region. To save on cost, an original sample of 150 vessels from the site of Chocolá was reduced to 43 using semi-quantitative testing to determine the presence of fatty acids and carbohydrates, indicating plant remains. Including these 43, because of Hershey's generosity, all 150 samples were analyzed by high-performance liquid chromatography by the method of Hurst. Cacao residues were found in ten vessels, or 6.7% of the 150 HPLC tested samples: (23.5% of the SQT-reduced sample) five bowls, three jars, and two plates, ranging in date from ca. 600 BCE–200 CE. Of the three sectors of the site, elite, administrative, and commoner/agricultural, distribution of all but one of the vessels was in the first and third sectors, suggesting consumption patterns in the ancient city and possibly, also, early intensive prehispanic arboriculture of cacao.